Generalization of Map Details within Computer Assisted Cartography - Yusuf, Matharuddin (Fakulti Ukur dan Harta Tanah, 1992)
subjectivity in generalization, the metamorphasis from manual to digital techniques in cartography has resulted in the development of computer algorithms designed to replicate many tasks previously performed by humans. In manual generalization cartographers have taken an intrisically hollistic approach where, when simpilifying manuscript line, many decisions a r e applied al once: the important characteristics are selected, these important characteristics might be exaggerated, and the unwanted detail is elimited all in one swoop of a pen. In contrast to manual generalization the computer approach requires separate algorithm to complete each component in the process: simplification, classification, simbolization, smoothing, diplacement and enhancement. Most of the research effort on automated generalization has been directed towards areas of linear simplification.